Exploring hemp farming as a sustainable agriculture in South Africa, using a social-ecological systems approach - Rightford, Brett Warwick Bevan (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPhil)--Stellenbosch University, 2020.